Juridical Implications of Land Ownership Status of Foreign Citizens Through a Nominee Agreement Based on the Concept of Legal Certainty - Ferniawan, Andi Erza (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to determine the juridical implications of the land ownership status of foreign citizens through nominee agreements based on the concept of legal certainty, to find out the legal consequences for perpetrators of nominee agreements for buying and selling land rights for foreign citizens. The approach method used in this study is research with sociological juridical methods, namely analyzing and providing answers about legal issues according to the intended target. Based on the research results, the authors draw the conclusion that 1). Whereas the name loan agreement in practice of land ownership by foreigners is juridically contrary to national land law, namely Article 9, Article 21 paragraph (1), and confirmed by Article 26 paragraph (1) of the UUPA. In addition, this practice is also contrary to the good faith principle of freedom of contract in contract law. In international civil law this practice constitutes legal smuggling of statutory regulations in land law, so that any legal smuggling including this name-borrowing agreement results in the cancellation of the relevant action, in international private law it is called fraus omnia corrumpt, meaning that legal smuggling results in the legal action in its entirety does not apply. 2). The legal consequence for the perpetrator of the nominee agreement on the sale and purchase of land rights for foreign nationals is that the mastery of land ownership rights by foreigners based on a name loan agreement (nominee) cannot be carried out because the agreement is considered invalid and does not meet the legal requirements of the agreement as stipulated in the provisions 1320 Civil Code. The legal consequences of the possession of land rights by foreigners based on a name loan agreement (Nominee) are null and void because the objective conditions are not fulfilled as determined by Article 1320 of the Civil Code.Keywords: Agreement; Land; Nominee.